1998
DOI: 10.1093/ndt/13.4.969
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide-binding protein is present in effluents of patients with Gram-negative and Gram-positive CAPD peritonitis

Abstract: Our data demonstrate that LBP is significantly elevated in the dialysis effluents of patients with CAPD-associated peritonitis caused by both gram-negative and gram-positive bacteria and might be used as a marker of intraperitoneal infection. Moreover, our findings support the concept that LBP enhances the effects of LPS on cytokine production by peritoneal macrophages. The function of LBP in gram-positive infection remains to be further elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…On the other hand, it was reported that in the presence of LBP the expression of pro‐inflammatory cytokines, such as IL‐1 β , IL‐6 and TNF‐ α , was all up‐regulated in the stimulation of LPS (Schäfer et al 1998). In contrast, an in vitro study found that IL‐1 β and cigarette smoke condensate induced the expression of LBP and CD14 by human airway epithelial cells (Regueiro et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it was reported that in the presence of LBP the expression of pro‐inflammatory cytokines, such as IL‐1 β , IL‐6 and TNF‐ α , was all up‐regulated in the stimulation of LPS (Schäfer et al 1998). In contrast, an in vitro study found that IL‐1 β and cigarette smoke condensate induced the expression of LBP and CD14 by human airway epithelial cells (Regueiro et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Zweigner et al [11] did not analyze LBP levels in regards to survival. One study performed in patients with chronic ambulatory peritoneal dialysis has described elevated LBP serum levels in peritoneal efflux of patients suffering from gram-negative and gram-positive peritonitis [14], but no corresponding LBP serum levels were provided. Kaden et al [10] described elevated LBP serum levels in 2 patients, who had undergone kidney transplantation, with Pneumocystis carinii pneumonia complicated by mycotic superinfection.…”
Section: Discussionmentioning
confidence: 99%
“…In one study performed in patients with chronic renal failure and peritonitis secondary to gram-positive agents, increased LBP serum levels have been observed in peritoneal fluid samples, but there were no data for concomitant serum levels [14]. Kaden et al [10] have reported an increase in LBP serum levels in 2 patients with Pneumocystis carinii and mycotic superinfection, who had undergone transplantation, but no detail is available for LBP serum levels in pure my- cotic infections.…”
mentioning
confidence: 99%
“…Thus, as for LPS, these factors include LPS-binding protein (LBP), which is synthesized mainly in hepatocytes and secreted into the bloodstream constitutively in small amounts (1 g/ml in mice) or in larger amounts (5 g/ml) as a class I acute-phase protein induced hours after challenge (37). Indeed, the concentration of this protein is minimal in uninflamed peritoneal fluid in vivo, although its abundant presence in inflamed peritoneal fluid in vivo (35) and its necessity for LPS activation of (murine) peritoneal macrophages have been demonstrated in vitro (15). LBP catalyzes the monomerization of LPS micelles and transfers the monomers as LPS-LBP complexes to another protein, CD14.…”
Section: Discussionmentioning
confidence: 99%